The Digital Fabric of Society: A Critical Analysis of Computer Networking’s Transformative Impact on Social Structures and Institutions - Kishor Kumar Bhupathi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of computer networking on contemporary society, analyzing its multifaceted influence across social, educational, and economic domains. Through a comprehensive article analysis of existing literature and emerging trends, the article explores how networking technologies have fundamentally altered communication patterns, educational paradigms, and commercial landscapes. The article investigates the dual nature of these transformations, addressing the opportunities created through enhanced connectivity and the challenges posed by digital divides, cybersecurity threats, and information integrity. Particular attention is paid to the role of networking in facilitating remote work adoption, democratizing education, enabling global commerce, and reshaping social movements. The article also considers the ethical implications of increased connectivity, including privacy concerns and the environmental impact of expanding network infrastructure. The findings suggest that while computer networking has become an indispensable catalyst for societal advancement, its evolution demands careful consideration of sustainability, equity, and responsible innovation. This article contributes to the growing body of literature on digital transformation by providing a holistic examination of networking’s societal impact and offering insights for future technological development.